Coverage of the first migrant caravans in the Mexican media - Ramos Rojas, Diego Noel (2022)
The media in Mexico have played a fundamental role in the social construction of the migratory reality and, in this regard, it was suggested that, on the issue of migrant caravans, some of them have performed thorough and rigorous coverage as a result of journalistic research, while others have not. The focus of this work is mixed and its scope is descriptive. Ten media outlets were analyzed, specifically 1,048 journalistic texts on the issue of migrant caravans, from October 2018 to February 2019. Quality indicators were used to analysis in the journalistic coverage and the results showed that certain media have a greater attachment to these indicators, while others tend to present a neutral-negative assessment.